Implementasi Keadilan Restoratif dalam Penyelesaian Tindak Pidana Ringan di Kepolisian Resort Tual Perspektif Hukum Pidana Islam - La Ode Arif Jaya; Hasbollah Toisuta; Abdul Jabar Abdu (Jurnal Hukum, Administrasi Publik dan Negara, 2026)
This study analyzes the implementation of restorative justice in resolving minor criminal offenses at the Tual Resort Police and examines it from the perspective of Islamic criminal law. The study is motivated by the development of a law enforcement paradigm that is no longer solely oriented toward punishment but also emphasizes the restoration of social relationships, victim protection, and the achievement of peace. In the Tual community, which continues to uphold customary, religious, and familial values, the restorative justice approach is considered more effective than formal judicial mechanisms. This study employs a normative-empirical method with a descriptive-qualitative approach. Primary data were obtained through interviews with investigators of the Tual Resort Police, customary leaders, religious leaders, and other relevant parties, while secondary data were collected through library research. The findings indicate that restorative justice at the Tual Resort Police has been implemented based on Indonesian National Police Regulation Number 8 of 2021 for minor criminal offenses, including petty theft, minor assault, defamation, and disputes among community members, through mediation involving families, customary leaders, and religious leaders. From the perspective of Islamic criminal law, this practice is consistent with the principles of ishlah, sulh, and maqāṣid al-sharī'ah, which emphasize peace, public welfare, and the restoration of social relationships. This study concludes that restorative justice at the Tual Resort Police reflects the harmonization of state law, customary law, and Islamic law in achieving a more humane and just resolution of criminal cases.